(untitled) (International journal of medical sciences, 2026)
Background: The incidence of early-onset coronary artery disease (CAD), manifesting as angina pectoris in young adults, is steadily rising. The interplay between cardiometabolic abnormalities and the sympathoadrenal system (SAS) is hypothesized to be a key driver of premature atherosclerosis and rapid disease progression. Objective: To investigate the correlation between cardiometabolic factors and functional disorders of the sympathoadrenal system in young patients with newly diagnosed angina pectoris, and to develop prognostic criteria for disease progression.